PENGARUH TAYANGAN IKLAN TELEVISI âCHIPS AHOY!â TERHADAP EKUITAS MEREK - Wijayanti, Rhisa (JUSS (Jurnal Sosial Soedirman), 2017)
Promotion through advertising is often done in an effort to develop the association, close relationship between brands with the consumers in order to create equity. The aim of this study was to determine the influence of Chips Ahoy! ad, Baking Show version towards brand equity to children. This study used the quantitative method to prove the hypothesis. The method which used to determine samples was done by Slovinâs formula and the sample was selected by proportional stratified random sampling. Respondents for this study were children from 1 to 6 elementary school grades with 214 people for the number population and 68 people were selected as sample respondents. Referring to the theory of Cognitive Development from Jean Piaget, respondents are researched by several age categories: pre-operational (2-7 years), concrete operations (8-11 years) and formal operation (12 years). The theory that used in this study was framed in Cognitive Response Models by Belch and Belch. The technique of data analysis used simple linear regression and the hypothesis testing used Pearson Product Moment Correlation test. Results showed that the effect was quite low but its still accordance with the theory that the process of thinking on children, in terms of the advertising perceive are changed along with the ages and the experiences. These results for this study was proven that showed the correlation coefficient R was 0.611 so it could be said that there were low effects but definite between the variables, and has a positive direction and significant of 0,001 < 0,05 which means Ha was accepted and Ho was rejected. The results of the regression test showed that the effect of Television Ad Chips Ahoy! towards the brand equity to the children was 37.3%.